Old bag of bones : a coyote tale - Stevens, Janet (New York : Holiday House, 1996)
Old Coyote doesn't appreciate the benefits of old age, so he goes to powerful Young Buffalo and asks for help.
Wilson's Children
Elem. School Library Collection
School Library Journal
2.7
K-3
Keywords: Shoshoni Indians -- Folklore; Tales -- Great Basin; Coyote (Legendary character) -- Juvenile literature; Shoshoni Indians -- Folklore; Tales -- Great Basin; Coyote (Legendary character); Shoshoni Indians -- Folklore; Folklore -- Great Basin; Coyote (Legendary character)